The impact of internal corporate governance structures on firm performance : evidence from publicly listed South African companies - Tshipa, Johannes (My University, 2014)
This study contains the findings of an examination conducted on the relationship between internal corporate governance structures and firm performance of those firms listed on South African Johannesburg Stock Exchange (JSE). Employing a sample of 137 South African (SA) listed firms from 2002 to 2011 (a total of 1370 firm-year observations) and corporate governance data collected directly from those companies‟ annual reports, the study seeks to determine the extent to which SA-JSE listed companies comply with King II recommendations of corporate governance and to ascertain whether such compliance necessarily translates into higher financial performance. Different from previous studies, the internal corporate governance-financial performance nexus is investigated over a 10-year panel study. In addition, the study uses accounting and market measures, return on assets (ROA) and Tobin‟s Q respectively, as proxies for financial performance. The findings suggest that the level of compliance has risen significantly over the period of examination, from 2002, when King II was adopted. However, substantial differences in the standards of corporate governance among SA listed firms still exist. Distinct from prior studies, an analysis was done of bothsmall and large companies to compare the respective levels of compliance. Notably, the results indicate that the level of compliance in large companies is relatively higher than that in small companies. In addition, the results also reveal that larger firms exhibit higher firm value as a result of higher compliance levels than their smaller counterparts. Results based on the multiple regressions provide mixed results on the impact of internal corporate governance on firm performance. First, regardless of the financial performance measure used, board size is statistically significant and positively related to both accounting measure (ROA) and market measure (Tobin‟s Q). Secondly, Chief Executive Officer (CEO) non-duality is statistically significant and positively associated with both proxies of performance measures. Thirdly, an independent non-executive director is only statistically significant and positively correlated with Tobin‟s Q. This could mean that the market perceives independent non-executive directors as a good practice to reduce agency problems. Fourthly, the presence of key internal board committees such as nomination, remuneration and audit is statistically significant and negatively related to ROA, but insignificant to Tobin‟s Q. iii Finally, board gender diversity, director share-ownership and frequency of board meetings have no impact on firm performance. As far as control variables are concerned, leverage, big 5 industry, big 4 audit firm size and firm size are statistically significant in both measures of firm performance. Interestingly, the findings also reveal that in South African firms only 9 per cent of board members are women. Findings based on a series of robustness or sensitivity analyses suggest that the empirical results are generally reported to be robust to potential endogeneity problems. In addition, the sample size is large enough to generalise the results. Empirical results indicate conclusively that internal governance mechanisms do have material effects on a firm‟s performance.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.